Kroppens tavshed: Refleksioner over performativitet - Heinrich, Falk (Peripeti, 2024)
The article critizises the tendency in performative theory to claim the body as an indeterminable zone of experience. Inspired by the system theory of Niklas Luhmann, Heinrich argues that it is necessary to analyze the interaction between communication, mind and body as a historically specific construct.